1992
DOI: 10.1901/jeab.1992.57-317
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Change and the Law of Effect

Abstract: Three experiments using multiple schedules of reinforcement explored the implications of resistanceto-change findings for the response-reinforcer relation described by the law of effect, using both steadystate responding and responding recorded in the first few sessions of conditions. In Experiment 1, when response-independent reinforcement was increased during a third component, response rate in Components 1 and 2 decreased. This response-rate reduction was proportionately greater in a component in which rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
68
1
10

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 33 publications
12
68
1
10
Order By: Relevance
“…Therefore, the assumed additivity of the effects of discontinuing the contingency and omitting reinforcers must be tested in factorial studies of resistance to change that vary the degree of response-reinforcer contingency with reinforcer rate constant and vary the reinforcer rate with the contingency constant. In a relevant study, Harper and McLean (1992) examined variations in reinforcer rate with the contingency constant. They arranged multiple VI VI schedules with thirty 6-sec reinforcers per hour in one component and thirty 2-sec reinforcers in the other component.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the assumed additivity of the effects of discontinuing the contingency and omitting reinforcers must be tested in factorial studies of resistance to change that vary the degree of response-reinforcer contingency with reinforcer rate constant and vary the reinforcer rate with the contingency constant. In a relevant study, Harper and McLean (1992) examined variations in reinforcer rate with the contingency constant. They arranged multiple VI VI schedules with thirty 6-sec reinforcers per hour in one component and thirty 2-sec reinforcers in the other component.…”
Section: Discussionmentioning
confidence: 99%
“…To control for frequency of encounter, we replicated the NC test of Experiment 1 with reinforcers that differed in magnitude but with the same reinforcer rates in the two components. Previous research has shown that differences in reinforcer magnitude between components affect resistance to change in much the same way as differences in reinforcer rates (e.g., Harper & McLean, 1992;Nevin, 1992;Nevin, Mandell, & Yarensky, 1981;Shettleworth & Nevin, 1965). Also, in two further replications, we imposed brief delays between responses and NC food presentations for two reasons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Na interrupção após o consumo agudo, observouse efeitos de maior perturbação no componente pobre no teste após 12 h, mas não após 36 h e o mesmo não foi visto após a administração crônica. Mesmo com as variáveis levantadas para melhor controle, como diferenças nas vias de administração (Brown, et al, 2000;Hall, et al, 2015;Mello 1976;Pohorecky, 1981) e aversividade da gavagem (Brown, et al, 2000;Hall, et al, 2015;Wallace, et al, 1990), ainda há a possibilidade dos resultados de retirada da droga como evento perturbador serem assistemáticos assim como os obtidos com há a administração da droga como evento perturbador (Cohen, 1989, Egli et al, 1992, Harper, 1999a, Pinskston, 2009 generalidade (e.g., Harper & McLean, 1992, Nevin, 1984. Assim, apesar das variáveis apontadas como importantes de serem investigadas, com uma replicação sistemática para dar força aos resultados obtidos, deve-se pontuar que apesar de uma vasta generalidade nos resultados obtidos com os mais diversos eventos perturbadores e da medida da resistência à mudança como proposta pelo momentum comportamental ser efetiva, existem especificidades que necessitam de cautela e de maiores investigações, salientando-se, portanto, o cuidado com a generalidade e verdade absoluta da teoria.…”
Section: Discussão Geralunclassified
“…Diante dos resultados dos experimentos de Nevin (1974), pode-se afirmar que, mesmo com algumas diferenças nos procedimentos empregados como, por exemplo, (1) na maneira de se delinear os componentes com maior ou menor taxa de reforço ou componentes "rico" e "pobre" (e.g., Bouzas, 1978;Harper, 1996;Harper & McLean 1992, Shettleworth & Nevin, 1965 e (2) nos eventos perturbadores empregados, os resultados são semelhantes.…”
Section: Introductionunclassified